The Effectiveness of Distribution of Zakat Funds on ZDC South Sumatra - Ali Mufrodi, Rinol Sumantri, Sri Iswati, (Opción, 2019)
The study aims to deepen how the effectiveness of the management of funds through the Zakat Development Community (ZDC) program and deepen how its impact to the mustahik by using the CIBEST approach (Center of Islamic Business Economic Studies). The mixed methodology method was adopted to achieve its objective. The result shows that the ZDC programs established by the National Zakat Agency have contributed well enough to improve welfare and reduce the poverty rate in Banyuasin district. In conclusion, Religious Obligatory program of Zakat Community Development (ZCD) has run effectively since the year 2013 till this time.